Falsidade, erro e loucura: os limites da racionalidade no sobre a certeza de L. Wittgenstein - Cesário, Igor de Souza (2022)
This dissertation aims to investigate the role of the concepts of falsehood, error and madness in Wittgenstein's On Certainty, even though these concepts are not explicitly addressed by the author. To do so, it is necessary to go through no less important steps; first, we seek to understand the way in which Moore's texts were important for Wittgenstein‘s ideas, then, we will connect those ideas to the discussion about truth theories, in order to understand what would be his position in relation to those theories. Finally, we will examine the concepts of falsehood, error and madness, in dialogue with commentators, aiming to understand Wittgenstein‘s final texts.